2018
DOI: 10.1111/echo.13857
|View full text |Cite
|
Sign up to set email alerts
|

E/eʹ ratio and left atrial area are predictors of atrial fibrillation in patients with hypertrophic cardiomyopathy

Abstract: An E/e' ratio ≥ 17, as an expression of left ventricular filling pressures with impact on the left atrium, and left atrial area ≥28 cm are strong predictors of AF in patients with HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Although conventional diastolic parameters may have limitations in assessing invasively measured filling pressures in HCM, E/e' ratio and left atrial size have been associated with adverse events including worsening heart failure, new-onset atrial fibrillation, and death. 5,[20][21][22][23] Therefore, effective treatments for oHCM should relieve LVOT obstruction, reduce mitral regurgitation, and improve diastolic function. In the current study, given that there was no change in mitral E wave velocity among patients who received mavacamten compared with placebo, the change in E/e' is predominantly driven by improvements in septal and lateral e' velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Although conventional diastolic parameters may have limitations in assessing invasively measured filling pressures in HCM, E/e' ratio and left atrial size have been associated with adverse events including worsening heart failure, new-onset atrial fibrillation, and death. 5,[20][21][22][23] Therefore, effective treatments for oHCM should relieve LVOT obstruction, reduce mitral regurgitation, and improve diastolic function. In the current study, given that there was no change in mitral E wave velocity among patients who received mavacamten compared with placebo, the change in E/e' is predominantly driven by improvements in septal and lateral e' velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive patients had a higher percentage of grade I or II dysfunction and a lower percentage of undetermined cases, according to the latest recommendations for diastolic function evaluation. 15 It should be noted that left atrial volume, an important parameter in the assessment of diastolic function, 15,25,26 was increased in both groups on average, with no significant difference between them. This means, in principle, that most patients had some degree of diastolic dysfunction, but it was better defined in hypertensive patients.…”
Section: Discussionmentioning
confidence: 87%
“…In a retrospective longitudinal analysis, Debonnaire et al showed that LA diameter and volume were positively correlated with new onset of AF in patients with HCM [ 55 ]. Interestingly, Costabel et al demonstrated that the E / e ´ ratio as well as LA enlargement were strong, independent predictors of AF [ 56 ]. Both elevated E / e ´ and LA enlargement were observed at baseline in the patients with HCM enrolled in mavacamten clinical studies.…”
Section: Observations/findingsmentioning
confidence: 99%